Enhanced Cell Division Is Required for the Generation of Memory CD4 T Cells to Migrate Into Their Proper Location - Sarkander, Jana; Hojyo, Shintaro; Mursell, Mathias; Yamasaki, Yuzuru; Wu, Tsung-Yen; Tumes, Damon J.; Miyauchi, Kosuke; Tran, Cam Loan; Zhu, Jinfang; Löhning, Max; Hutloff, Andreas; Mashreghi, Mir-Farzin; et al. (Frontiers in Immunology, 2020)
CD4 T cell memory is fundamental for long-lasting immunity and effective secondary responses following infection or vaccination. We have previously found that memory CD4 T cells specific for systemic antigens preferentially reside in the bone marrow (BM) and arise from splenic CD49b+T-bet+ CD4 T cells. However, how the precursors of BM memory CD4 T cells are generated during an immune reaction is unknown. We show here that BM memory precursors are generated via augmented rates of cell division throughout a primary immune response. Treatment with the cytostatic drug cyclophosphamide or blockade of the CD28/B7 co-stimulatory pathway at the beginning of the contraction phase abrogates the generation of BM memory precursors. We determine that, following a critical number of cell divisions, memory precursors downregulate CCR7 and upregulate IL-2Rβ, indicating that loss of CCR7 and gain of IL-2 signal are required for the migration of memory precursors toward the BM.